Philippa M. Steele (ed.). Understanding Relations Between Scripts. The Aegean Writing Systems. - Dickinson , Oliver (Journal of Greek Archaeology, 2018)
This book is based on the papers given at a conference in Cambridge, March 20-21, 2015, held in memory of Anna Morpurgo Davies, on various aspects of the prehistoric Aegean writing systems (Cretan Hieroglyphic, Linear A and Linear B) and their Cypriot relatives, including not only the material classified as Cypro-Minoan, but the Cypriot syllabary that developed from this in the early Iron Age and went on in use well into historical times, used to write both Greek and at least one non-Greek language of the island.